Sprawozdania Zarządu Miejskiego miasta Olsztyna do Biura Prezydialnego Krajowej Rady Narodowej z 1945 r. Źródła do dziejów administracji polskiej na Ziemiach Odzyskanych po II wojnie światowej - Syrwid, Robert (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
In the article, three reports of Olsztyn City Management prepared for the Presidium Office of the State National Council and covering October, November and December 1945 are presented. The published descriptive-statistical reports, containing information about the most important elements of the process of reconstruction and about living conditions of the population, constitute a valuable material for research on the history of one of the most important Polish urban centers on the so-called Regained Territories after World War II
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne